Attitudes Toward Animal Dissection and Animal-Free Alternatives Among High School Biology Teachers in Switzerland - Zemanova, Miriam A. (Frontiers in Education, 2022)
Animal dissection has been a traditional teaching tool in biology for centuries. However, harmful animal use in education has raised ethical and environmental concerns in the last decades and led to an ongoing debate about the role and importance of animal dissection in teaching across all education levels. To understand the current status of dissection in secondary education and the attitudes towards humane teaching alternatives among the educators, I conducted a survey – for the first time – among high school biology teachers in Switzerland. The specific aims of this study were i) to explore the extent of animal or animal parts dissection in high school biology classes, ii) to understand the attitudes and experiences of high school biology teachers towards dissection and animal-free alternatives, and iii) to gain some insight into the circumstances hindering a wider uptake of alternatives to animal dissection in high school education. In total, 76 teachers participated in the online survey. The vast majority (97%) of the participants reported using animal dissection in their classes. The responses also revealed that a large proportion of the teachers consider animal-free alternatives inferior teaching tools in comparison with dissection. As the obstacles to adopting alternatives were most often listed the lack of time to research other methods, high costs, and peer pressure. In conclusion, the wider uptake of humane teaching methods would require financial support as well as a shift in the attitudes of high school biology teachers.